Statin prescription by Croatian family doctors : lack of systematic proactive approach to cardiovascular disease prevention - Vrdoljak, Davorka (Array, 2009)
Abstract: The aim of this study was to investigate statin prescription by family doctors (GP) in primary (PP) and secondary (SP) prevention of cardiovascular diseases (CVDs). Patients’ socio-demographic data, total cholesterol (TC) and LDL-cholesterol (LDL-C) thresholds for statin prescription, indications, data on GP and practices were registred. Statins were prescribed in 11.2% enlisted patients (64.11% PP, 35.88% SP), mostly aged 70+. In PP, thresholds were TC 6.2±1.09 mmol/L, LDL-C 3.6 mmol/L, in SP 5.4±1.26 mmol/L, 2,7mmol/L, respectively. Most frequently prescribed statin in PP was 10 mg atorvastatin (49.28%), in SP it was 20 mg simvastatin (48.36%). Participating GPs were women, aged 39±5.49, working for 13±6 years, the average number of enlisted patients per GP 1562±299. There was statisticaly significant difference in statin prescription in PP (c2=752.9; p<0.001) and SP (c2=64; p<0.001). Statin prescription in PP is due to pharmaceutical marketing and lack of independent continuing medical education. The fact that statins are most frequently prescribed in patients aged 70+ (35.28% in PP, 49.35% SP) reveals lack of preventive proactive CVDs approach in younger age groups, which is concerning